Properties of a simian virus 40 mutant T antigen substituted in the hydrophobic region: defective ATPase and oligomerization activities and altered phosphorylation accompany an inability to complex with cellular p53. - Tack, L C (1989)
We have analyzed the biochemical properties of a nonviable simian virus 40 (SV40) mutant encoding a large T antigen (T) bearing an amino acid substitution (Pro-584-Leu) in its hydrophobic region. Mutant 5080 has an altered cell type specificity for transformation (transforming mouse C3H10T1/2 but not rat REF52 cells), is defective for viral DNA replication, and encodes a T that is unable to form a complex with the cellular p53 protein (K. Peden, A. Srinivasan, J. Farber, and J. Pipas, Virology 168:13-21, 1989). In this article, we show that 5080-transformed C3H10T1/2 cell lines express an altered T that is synthesized at a significantly higher rate but with a shorter half-life than normal T from wild-type SV40-transformed cells. 5080 T did not oligomerize beyond 5 to 10S in size compared with normal T, which oligomerized predominantly to 14 to 20S species. In addition, the 5080 T complex had significantly decreased ATPase activity and had a 10-fold-lower level of in vivo phosphorylation compared with that of normal T. Two-dimensional phosphopeptide analysis indicated several changes in the specific 32P labeling pattern, with altered phosphorylation occurring at both termini of the mutant protein compared with the wild-type T. Loss of p53 binding is therefore concomitant with changes in ATPase activity, oligomerization, stability, and in vivo phosphorylation of T and can be correlated with defective replication and restricted transformation functions. That so many biochemical changes are associated with a single substitution in the hydrophobic region of T is consistent with its importance in regulating higher-order structural and functional relationships in SV40 T.